Cloning and expression analysis of the glucocorticoid receptors and the effects of cortisol in sex differentiation in protogynous hermaphroditic swamp eel, Monopterus albus - Su, Jialin; Sun, Lei; Yang, Jiaqi; Yao, Weizhi; Xu, Hongyan; Feng, Ke (Frontiers in Marine Science, 2025)
Cortisol is the major glucocorticoid, which is considered to be a key factor linking the environmental stress and sex differentiation in teleosts. In the present study, we explored the possible role of cortisol in sex differentiation in a protogynous hermaphroditic swamp eel, Monopterus albus. We cloned and characterized the full-length cDNA sequences of glucocorticoid receptor genes, gr1 and gr2. A novel alternative splicing variant (gr1b) was also discovered, which lacked a 27-bp nucleotide insertion in gr1, resulting in a nine-amino-acid deletion in GR1. Real-time PCR indicated that swamp eel gr1a mainly expressed in the brain; gr1b mainly in the spleen, head kidney, kidney and muscle; gr2 mainly in the muscle. During female-to-male sex reversal, the expression levels of gr1a and gr1b decreased significantly at the stage of ovotestis III, and gr2 showed a trend of increase, and increased significantly in the testis. In the brain, acute heat stress up-regulated significantly the expression of gr1a and gr1b, while had no significant effect on gr2. However, in the ovary, heat stress only up-regulated significantly the expression of gr1b at 12 h. Serum cortisol concentration increased significantly by heat stress at 1 h, and returned to normal levels at 6 and 12 h. Cortisol injection up-regulated significantly the expression levels of gr1b and gr2, while had no significant effect on gr1a in the ovary. At the same time, cortisol injection down-regulated significantly the expression of cyp19a1a, and only decreased significantly the expression of foxl2 at 6 and 12 h. Cortisol injection up-regulated significantly the expression of dmrt1a at 6, 24 and 48 h, while only increased the expression of gsdf at 6 h. The results indicate that cortisol and GRs may play roles in sex differentiation by the regulation of gonadal differentiation-related gene expression in swamp eel.